“The Writer Is Essentially Indiscrete.” On the Literary Gossip of a Dutch Literary Celebrity - Bax, Sander (Werkwinkel, 2017)
In contemporary media culture, literary writers arouse the fascination of media fans by awakening in them the desire for the authentic by publishing autobiographical novels or other forms of life narrative. In doing so, they run the risk of becoming part of media’s large gossip mechanism that plays such a central role nowadays. The public conversation about the books of writers such as the Dutch author Connie Palmen - whose Logboek van een onbarmhartig jaar will be the main case study of this article - becomes focused on the elements of truth and authenticity and ignores the literary or fictional construction of the work. This article discusses the question whether this leaves any room for contemporary star authors to distinguish themselves from media gossipers.